ANALYSIS OF PORTLAND POZZOLAN CEMENT (PPC) AND DOLOMITE FOR CLAY STABILIZATION AS SUBGRADE - Lola Cassiophea (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
The road surface is often suffered from crack caused by high shrinkage property of clay as base soil. One of several methods to overcome this is by stabilizing it by adding Portland Pozzolan Cement (PPC) and dolomite in the clay. The method used in this research is experiment based on trial and error method. Mixture percentage used is 0%, 5%, 10%, 15% dan 20 % from total mixture weight, with hardening time 0 day, 7 days, 14 days, 21 days and 28 days. The results show that the more PPC mixture and dolomite percentage, the stronger the soil support strength (CBR value). The best result from this research is the mixture of clay, PPC and dolomite at 20% with hardening time of 28 days and CBR = 52,2757% (increases 1088,4211%).